Brain training in progress: a review of trainability in healthy seniors - Buitenweg, Jessika I.; Murre, Jaap M.; Ridderinkhof, K. Richard (Frontiers in Human Neuroscience, 2012)
The cognitive deterioration associated with aging is accompanied by structural alterations and loss of functionality of the frontostriatal dopamine system. The question arises how such deleterious cognitive effects could be countered. Brain training, currently highly popular among young and old alike, promises that users will improve on certain neurocognitive skills, and this has indeed been confirmed in a number of studies. Based on these results, it seems reasonable to expect beneficial effects of brain training in the elderly as well. A selective review of the existing literature suggests, however, that the results are neither robust nor consistent, and that transfer and sustained effects thus far appear limited. Based on this review, we argue for a series of elements that hold potential for progress in successful types of brain training: (i) including flexibility and novelty as features of the training, (ii) focusing on a number of promising, yet largely unexplored domains, such as decision-making and memory strategy training, and (iii) tailoring the training adaptively to the level and progress of the individual. We also emphasize the need for covariance-based MRI methods in linking structural and functional changes in the aging brain to individual differences in neurocognitive efficiency and trainability in order to further uncover the underlying mechanisms.